Assessment of peripheral blood neutrophil respiratory burst, phagocytosis and apoptosis in obese non-insulin dysregulated horses. (October 2020) - Salinas, Constanza; Espinosa, Gabriel; Morales, Natalia; Henríquez, Claudio; Morán, Gabriel; Gajardo, Gonzalo; Uberti, Benjamin
Abstract: Obesity is a highly prevalent condition in horses. Dysfunctional neutrophil activity has been reported in metabolically healthy obese humans, but minimal data exist regarding horses. The present study evaluated the effect of obesity on apoptosis, phagocytosis and oxidative burst activity of peripheral blood neutrophils from lean and obese non-insulin dysregulated horses. Seven lean (BCS, body condition score 4–6/9) and five obese (BCS 8–9) horses were enrolled in the study. All animals underwent two metabolic tests (OGT, oral glucose test; IRT, insulin response test) before their selection to ensure their metabolic status (non-insulin dysregulated). A single blood sample was obtained from each horse, and a discontinuous density gradient was carried out to isolate neutrophils. Phagocytosis, apoptosis and reactive oxygen species (ROS) production assays were performed for each animal. All statistical analyses were performed with unpaired two-tailed t -tests. Results indicate that neutrophils from obese non-insulin dysregulated horses have a significantly increased ROS production ( P < .0001), with no changes observed on phagocytosis ( P > .05) or apoptosis (P > .05) when compared to the control group. In conclusion, our results demonstrate that obesity per se, in absence of other endocrine disorders, alters neutrophil reactive oxygen species production. More research is needed to understand the role of obesity on the equine immune system of horses, and its role in the development of endocrine disorders. Highlights: Blood neutrophil respiratory burst is altered in obese non-insulin dysregulated horses. Obesity does not affect blood neutrophil lifespan. Obesity does not affect blood neutrophil phagocytic capacity.